Physical, Mental, and Emotional Fatigue Experienced by IT Students During Covid-19 Pandemic - Mariappan, Saunthariya; Mohamad Nordin, Norhisham (Journal of ICT in Education, 2021)
The 2019 Coronavirus Disease (COVID-19) pandemic has significantly affected Malaysia’s higher education sector. It also creates an incentive for the restoration of the school sector and the establishment of revised programmes and evaluations. Higher learning institutions begin to embrace virtual learning which forces the students to adopt new types of learning in a short period. This research paper presents an empirical investigation of physical, mental and emotional fatigue experienced by undergraduate Information Technology (IT) programme students during the COVID-19 pandemic. A set of questionnaires was developed using the ZEF Scale focusing on physical, mental and emotional fatigue. To validate the questionnaires, the item questions were administered by the three education technology domain experts, from the Computing Department, Faculty of Arts, Computing, and Creative Industry (FSKIK), Universiti Pendidikan Sultan Idris (UPSI). This study involved a total of 230 undergraduate students from the IT program. The responders were administered with the questionnaire using Google Form. The collected data had been analysed using descriptive analysis with frequency and percentage, correlation analysis with frequency and percentage, validity, and reliability of each question. The Pearson correlation (r) demonstrated that the study was significant. The majority of undergraduate IT programme students were experiencing physical fatigue (r=0.984), emotional fatigue (r=0.965) and mental fatigue (r=0.937) while attending classes virtually. Thus, with this study, we support the notion that the undergraduate IT programme students were experiencing physical, mental and emotional fatigue while attending the classes online during the COVID-19 pandemic.